SOSIALISASI PEMANFAATAN BATANG BUAH NAGA SEBAGAI SUMBER ENERGI LISTRIK - Wahyu Arini; Tri Ariani; Endang Lovisia (LP4MK STKIP PGRI Lubuklinggau, 2021)
This program aims to socialize the use of dragon fruit stalks as a source of electrical energy. The implementation of this service was carried out in Megang Sakti III Village, Megang Sakti District, Musi Rawas Regency, with the target of the Megang Sakti III Village PKK Team. Dragon fruit plants are one of the leading commodities in Megang Sakti III Village, this is marked by the number of dragon fruit plantations along the Megang Sakti District area so that it attracted the TIM's interest in carrying out PPM activities in the village by socializing the benefits of dragon fruit stems as a source of electrical energy by parallel circuit concept as well as dynamic electricity. The electrical circuit from dragon fruit stalks is an alternative source of renewable energy that can ease people in overcoming electrical problems in everyday life. Due to the increase in electricity rates plus there are still many Indonesians, especially in rural areas who have not been touched by electricity, it is necessary to develop an alternative source of electrical energy that is easy and cheap and by utilizing the available local potential. dragons arranged in parallel are proof that dragon fruit stalks can be used as a source of renewable electrical energy, so that people realize that there are many beneficial things that can be obtained from dragon fruit plants besides consuming the fruit.